Seesjärvi Karelian Transcripts - Sarhimaa, Anneli (Zenodo, 2022)
This data set contains the word, rtf, and pdf transcriptions of the fieldwork interviews conducted in 1989-1991 by Anneli Sarhimaa (https://www.sneb.uni-mainz.de/team/anneli-sarhimaa/) among speakers of South Karelian dialects around lake Segozero (Fin. Seesjärvi) in the Republic of Karelia, the Russian Federation. The interviews were made to gain authentic empirical research material on the linguistic state of the Karelian language at the time and on the ways the community-wide Karelian-Russian biligualism and the rather widespread knowledge of the closely related Finnish language were reflected in everyday language use.